Los representantes del poder religioso en la epigrafía romana del noroeste hispano - García Martínez, Sonia María (Estudios humanísticos. Geografía, historia y arte, 1997)
The figure of the spiritual guiding is very important in the roman world. In this we article going to analize its presence in the epigraphic monuments of the Hispanic-roman Northwest.